Pandemic pushes polarisation: The Corona crisis and macroeconomic divergence in the Eurozone - Claudius Gräbner; Philipp Heimberger; Jakob Kapeller (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2020)
Die Wirtschaftswissenschaft spielt eine wesentliche Rolle im Drama der multiplen Gesellschaftskrise: Ihre dominanten Strömungen folgen einer ideologischen marktfundamentalen Erzählung, die die Krisen nicht adäquat erklären kann und sie dadurch verschärft. Ziel des Beitrages ist es, einen theoretischen und konzeptionellen Rahmen zu entwickeln, mit dem diese Erzählung expliziert und analysiert werden kann. Es kann etwa gezeigt werden, dass der Kern der Erzählung, "der Markt", in vielfachen sich widersprechenden Bedeutungen und Metaphern personifiziert und naturalisiert wird. Das Narrativ folgt einem dualen Weltbild, dass antagonistische Gegensätze konstruiert. So wird die Vielfalt an alternativen Möglichkeiten des Wirtschaftens, die durch die Menschen gestaltet und verantwortet werden, verschleiert.This paper discusses the uneven consequences of the macroeconomic fallout from the coronavirus and related economic policy responses against the background of an analysis of longer-term macroeconomic divergence in the Eurozone. We show that the macroeconomic impact of the Corona crisis is estimated to be more severe in Southern Eurozone countries than in Northern Eurozone countries, which further reinforces the tendency of an increasing economic polarisation. This polarisation process can be traced back to existing differences in production structures and uneven vulnerabilities of the underlying growth models. As a consequence, any policy response to the Corona crisis that does not take the deeper problems of structural polarisation into account will suffer from limited impact in the medium to long run.
Keywords: E6; F4; O3; 330; Polarisation; Coronavirus; Eurozone